The Associations of Polygenic Scores for Risky Behaviors and Parenting Behaviors with Adolescent Externalizing Problems - Ksinan, Albert J; Smith, Rebecca L; Barr, Peter B; Vazsonyi, Alexander T (Behavior genetics, 2022)
The current study focused on longitudinal effects of genetics and parental behaviors and their interplay on externalizing behaviors in a panel study following individuals from adolescence to young adulthood. The nationally representative sample of Add Health participants of European ancestry included N = 4142 individuals, measured on three occasions. Parenting was operationalized as experiences with child maltreatment and maternal closeness. Externalizing problems were operationalized as alcohol use, cannabis use, and antisocial behaviors. Genetic effects were operationalized as a polygenic score (PGS) of risky behaviors. The results showed significant effects for child maltreatment, maternal closeness, and PGS, above and beyond other factors and previous levels of externalizing behaviors. Furthermore, maternal closeness was found to negatively correlate with PGS. No significant interaction effects of parenting and PGS were found. The results underscore the joint independent effects of parenting and genetics on the change in externalizing behaviors from adolescence to young adulthood.
Keywords: Multifactorial Inheritance; Antisocial Personality Disorder; Humans; Longitudinal Studies; chování mladistvých; dítě; Child; mladý dospělý; dospělí; lidé; Polygenic score; Risk-Taking; Adult; longitudinální studie; Adolescent Behavior; Parenting; Adolescent; Externalizing behavior; multifaktoriální dědičnost; riskování; Young Adult; Risky behaviors; rodičovství; Substance use; asociální osobnost; mladiství